The mental encyclopaedia and the implications for vocabulary work in the teaching of foreign languages - Grünewald, Andreas; Roviró, Barbara (Pulso. Revista de educación, 2007)
Taking mental lexicon research, its results and assumptions of plausibility as a starting point, the authors show implications for the teaching and learning of vocabulary in the Spanish as a foreign language classroom. First, they examine the role of the native mental lexicon in speech production and comprehension. Second, they focus on the multilingual mental lexicon and hypotheses on storing and retrieving words from it. As a result, the authors develop a typology of exercises for the foreign language classroom and with the help of vivid examples put forward ideas for effective vocabulary teaching and learning.
Keywords: Vocabulary; Spanish as a Foreign Language; Mental Lexicon